The Current State of the Teaching the Russian Language in the Multicultural Russian School - Natalia I. Kytina; Elizaveta A. Khamraeva (Peoples' Friendship University of Russia (RUDN University), 2021)
Although it is commonly known that the dominant trend in the development of modern post-industrial society is globalization, today we can already talk about glocalization as a bidirectional process of integration and localization, complementary to the dialectical development of mankind. This process implies the unification of all spheres of social life in a single global space and the isolation of individual regions and ethnic groups as a protective reaction to preserve their uniqueness and identity. The described social trends are now becoming decisive for the development of the education system as the main social institution. Migration processes and related problems of integrating migrants into a new society, preserving the national language and culture, searching for identity - all these phenomena necessitate innovative methodological solutions that should be implemented in the context of learning the Russian language at a multicultural Russian school. The article considers topical problems related to the implementation of the program of teaching the Russian language in a multicultural environment. The authors propose a conceptual definition of a multicultural school. They analyze the pedagogical experience of individual educational institutions developing their own training methods for use in a multicultural environment. This analysis makes it possible to identify socio-adaptive, cultural, psychological and linguistic aspects of teaching Russian in a multicultural school. Along the way, an increase in the psychoemotional burden of teachers working in multi-ethnic classes is noted. Additionally, the effective experience of implementing preschool language training of non-native speakers in the Moscow region is analyzed. In line with the above, the authors review the current situation with regard to teaching the Russian language in the multiethnic regions of Russia through the example of the Republics of Sakha (Yakutia) and Tatarstan. In particular, it is noted that for the regions of the Russian Federation it is methodologically incorrect to use the term multicultural school, since in the national constituent entities of the Russian Federation there is a special type of national school, and a program for studying Russian as a non-native language is also being implemented.